A step towards enhancing the efficiency of biofilm mediated degradation of brilliant green dye in packed bed bioreactor: Statistical and toxicity analysis - Tripathi P.; Tiwari S.; Sonwani R.K.; Singh R.S. (My University, 2025)
This study aims to investigate the biodegradation of brilliant green (BG) dye in a packed bed bioreactor (PBBR) using Bacillus lichenifomis immobilized polyurethane (PU) foam as support material. The operating process parameters (e.g., pH, dye concentration, and inoculum dose) were optimized using response surface methodology (RSM) and artificial neural network (ANN). A sensitivity analysis reveals that pH has comparatively more significance (46 %) than the other parameters. Further, PBBR was continuously operated at various inlet feed flow rates (10–50 mL/h) under optimum conditions for 60 days. Maximum removal efficiency (RE) and elimination capacity (EC) were found to be 91.2 % and 88.0 mg/L.d, respectively. Monod and Andrews-Haldane models were applied for kinetic study and kinetics parameters μmax and Ks was found to be 0.125 per day and 38.9 mg/L for Monod and 0.175 per day and 45.1 mg/L for Andrew – Haldane model respectively. UV–vis and FTIR analysis confirmed the successful biodegradation of BG dye. Stress caused by BG dye was assessed by chlorophyll (a and b) and carotenoid content. Superoxide dismutase (SOD) activity was analyzed for biologically treated samples. Bacterial toxicity study reveals that biologically treated samples showed significantly less bioluminescence inhibition. © 2023 The Institution of Chemical Engineers